UPAYA PENYADARAN MASYARAKAT TERHADAP KELESTARIAN SPESIES ENDEMIK SUNGAI SERAYU IKAN UCENG (Nemachilus fasciatus C.V.) DI KABUPATEN BANYUMAS - Yogi Putranto (Dinamika Journal : Pengabdian Masyarakat, 2019)
A Research on efforts to raise awareness of fishing communities towards endemic fish of the Serayu Uceng River (Nemachilus fasciatus C.V.) as well as the rule of law regarding destructive fishing has been carried out at the Banyumas District Fisheries Office. The purpose of this research is to make the community aware of the sustainability of uceng fish resources. The research was conducted through a material transfer method for 30 people from the environmentally responsible anglers community and 10 village heads in the Banyumas Regency. The results showed that there were 3 people who did not yet know the rule of law regarding destructive fishing (93.33%). The results of the study also recommend the importance of forming a Community Watch Group (POKMASWAS) in monitoring destructive fishing in the Serayu River. Efforts to continuously monitor fisheries resources can create sustainable fisheries resources.Keywords: uceng fish, Serayu river, destructive fishing, community watch group